PENERAPAN STRATEGI QUIZ TEAM DALAM MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI IPA 1 SMA NEGERI 2 TAMBANG - Ade Putri; Kartini Kartini; Syofni Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract This research aims to improve learning process and mathematics learning outcomes in SMA Negeri 2 Tambang by implementing Quiz Team strategy in cooperative learning model. Subjects of the research were students grade XI IPA 1 who have the academic ability of the heterogeneous. This research is a classroom action research with two cycles. Each cycle has four stages, the stages are planning, action, observation and reflection. The results showed the activity of teachers and students have done well after doing the action. An increase in the number of students who achieved at UH KKM end of each cycle compared to the number of students who achieve KKM on base score, increasing the number of students who scored 20 and 30 compared to the development of the number of students who received grades 5 and 10 as well as the increase in the average value of students from the first cycle to the second cycle. Results of this research indicate that the application of Quiz Team strategy in cooperative learning model can improve learning process and the mathematics learning outcomes of students grade XI IPA 1 SMA Negeri 2 Tambang in the first semester academic year 2013/2014. Key words: Learning process, Mathematics learning outcome, Cooperative learning, Quiz Team Strategy, Classroom action research.